Epicatechin gallate and its analogues interact with sortase A and β-lactamase to suppress Staphylococcus aureus virulence - Teng, Fei; Wang, Lihui; Wen, Jingyao; Tian, Zizeng; Wang, Guizhen; Peng, Liping (Frontiers in Cellular and Infection Microbiology, 2025)
Staphylococcus aureus sortase A can anchor virulence proteins, which are responsible for bacterial adhesion, biofilm formation, and inflammation, to the cell membrane surface. The ability of β-lactam antibiotics to combat S. aureus infections is limited by the presence of β-lactamases in this pathogen. In this study, we determined that epicatechin gallate (ECG) and its analogues inhibited the transpeptidase activity of sortase A by interacting with it directly, and the biofilm formation and adhesion abilities of the bacterium decreased after treatment with ECG and its analogues. Additionally, ECG bound to β-lactamase and reduced its ability to hydrolyze nitrocefin. Furthermore, ECG synergized with ampicillin (Amp), enhancing its bactericidal effects and inhibiting the formation of persisters. ECG did not affect the expression of sortase A or β-lactamase but significantly alleviated the cytotoxicity of S. aureus USA300. ECG alone or combined with Amp in vivo improved the survival of mice infected with S. aureus USA300, alleviated pathological tissue damage and pulmonary edema, and reduced the extent of inflammation and level of colonization. The results of this study indicate that the active ingredients of green tea, especially ECG, have the potential to be developed as anti-S. aureus infection agents.